He got game [videorecording (DVD)] - Lee, Spike; Washington, Denzel, 1954-; Allen, Ray, 1975-; Jovovich, Milla; Dawson, Rosario (Touchstone Home Entertainment : Distributed by Buena Vista Home Entertainment, 1998)
A prisoner is granted a furlough in hopes of persuading his estranged son, the country's top high school basketball player, to attend the governor's alma mater.